1999
DOI: 10.1016/s0925-4773(99)00211-7
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Leopard gene as a component of the putative reaction-diffusion system

Abstract: It has been suggested, on a theoretical basis, that a reaction-diffusion (RD) mechanism underlies pigment pattern formation in animals, but as yet, there is no molecular evidence for the putative mechanism. Mutations in the zebrafish gene, leopard, change the pattern from stripes to spots. Interestingly each allele gives a characteristic pattern, which varies in spot size, density and connectivity. That mutations in a single gene can generate such a variety of patterns can be understood using a RD model. All t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
127
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 14 publications
5
127
1
Order By: Relevance
“…Note the transition of the stripes by changing the ␦ u (or ␦ v ) from O to A (or I ). Quantitatively, the same results were obtained even if we used different reaction terms (Shoji et al, 2002;for example, f(u,v) [Kondo and Asai, 1995;Asai et al, 1999]) or a different form of anisotropy (for example, D ϭ 1 ϩ ␦ cos 2 , ϭ u or v, as proposed by Kobayashi, 1993).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Note the transition of the stripes by changing the ␦ u (or ␦ v ) from O to A (or I ). Quantitatively, the same results were obtained even if we used different reaction terms (Shoji et al, 2002;for example, f(u,v) [Kondo and Asai, 1995;Asai et al, 1999]) or a different form of anisotropy (for example, D ϭ 1 ϩ ␦ cos 2 , ϭ u or v, as proposed by Kobayashi, 1993).…”
Section: Discussionsupporting
confidence: 67%
“…To show that the result of the simulation is not specific to a particular equation, but rather to the general property of the RD pattern, we used three different forms of reaction terms that satisfy the Turing conditions (e.g., Murray, 1989) and form stripes in a two-dimensional field. The equations we tested are the models of activator-depleted substrate type (Gierer and Meinhardt, 1972), linear type with saturation (Kondo and Asai, 1995;Asai et al, 1999), and activator-inhibitor type (Gierer and Meinhardt, 1972). Because we obtained basically the same results from all of these models, only the results from the activator-depleted substrate type model are shown below.…”
Section: Reaction-diffusion Modelmentioning
confidence: 99%
“…This mechanism implies that R8s are chosen earlier than previously thought, during the initial process of induction. Unlike previous scenarios (8,9), the switch and template mechanism predicts that genetically identical tissue can readily sustain different patterns depending on initial conditions, as we verify experimentally.…”
supporting
confidence: 49%
“…For example, a wide range of mutant strains of zebrafish have been identified that exhibit altered pigmentation patterns. In the case of mutations of one gene in particular, the leopard gene, it is possible to match the observed allelic sequence by smoothly varying a parameter in a Turing-type model (19). This lends further support to the notion that a self-organizing process is at work in this system.…”
Section: If Morphogens Cued Cell Differentiation Then Natural Pattersupporting
confidence: 54%